Development of Fringe Image Processing Algorithms for Tomograpic Reconstruction of Temperature Field in an Axisymmetric Medium - Khaleel, Ibtihal (Indonesian Journal Publisher, 2024)
This work is part of the development of algorithms and digital tools for the tomographic reconstruction of the (3D) temperature field from images resulting from thermal metrology based on two optical techniques (Moire deflectometry and holographic interferometry). It is intended not only for digital scientists and image processing specialists but also for researchers and practitioners in instrumentation and measurement by non-invasive techniques in general and in thermal metrology by optical techniques in particular Tomography by optical techniques of axisymmetric transparent media, the main subject of application of this thesis, is a perfect example of an imaging system based on an elementary mathematical property (the Abel transform and its inverse in this case). This property comes up against in its practical application the hypersensitivity to noise and problems due to the intrinsic characteristics of this transform. However, the study of transparent media such as air in our case, which does not present any radiative, absorption or diffusion properties, makes the images resulting from optical techniques unusable only after a treatment which precedes the inverse calculation of the Abel transform. This treatment thus limiting the development of 3D imaging requires special attention. Furthermore, the tomographic reconstruction of the temperature field of such an environment will be done in two processing parts, the first of which will focus on the analysis of mud figures, while the second is dedicated to solving the inverse problem generated by the Abel transform.